Pengaruh Dokter Detektif (Doktif) Dalam Bisnis Skincare : Antara Kepercayaan Konsumen Dan Kepatuhan Hukum - Diandra Azzahra Isabella; Fazara Aspasari; M. Abdilah Maghfiro (PT. Hasba Edukasi Mandiri, 2025)
Influencers on social media have a significant impact on public perception, especially when it comes to skincare and beauty product education. The foundation of this study is user protection against the use of overly dramatic claims (overclaims) in skincare advertising that may be harmful to consumers, such as exaggerated claims for skincare ingredients. This research aims to explore the role of influencers in educating the audience on the TikTok account